2005
DOI: 10.1159/000086974
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcome of Inoperable Non-Small Cell Lung Cancer Patients Receiving Conventional Dose Epirubicin and Paclitaxel as First-Line Treatment

Abstract: Objective: High-dose epirubicin was shown to be effective in the treatment of inoperable non-small cell lung cancer (NSCLC). Paclitaxel is synergistic to a conventional dose of anthracyclines in the treatment of advanced cancer. A phase II study was designed to test the effectiveness of combining paclitaxel with a conventional dose of epirubicin in inoperable NSCLC patients. Methods: Eligibility criteria included inoperable stage IIIB or IV NSCLC patients, Eastern Cooperative Oncology Group performance status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Although the objective response rate of conventional-dose epirubicin (60-90 mg/m 2 per cycle) was generally lower [8,9], these lower dose of epirubicin may allow safer combination with other third-generation agents. We recently reported that epirubicin 70 mg/m 2 plus paclitaxel, 175 mg/m 2 every 3 weeks produced partial response in 17 of 38 patients with stage IIIB/IV NSCLC (response rate 44.7%), and the median overall survival was 11.9 months [10]. The above data suggest that conventional-dose epirubicin may be effective in NSCLC treatment.…”
Section: Introductionmentioning
confidence: 86%
“…Although the objective response rate of conventional-dose epirubicin (60-90 mg/m 2 per cycle) was generally lower [8,9], these lower dose of epirubicin may allow safer combination with other third-generation agents. We recently reported that epirubicin 70 mg/m 2 plus paclitaxel, 175 mg/m 2 every 3 weeks produced partial response in 17 of 38 patients with stage IIIB/IV NSCLC (response rate 44.7%), and the median overall survival was 11.9 months [10]. The above data suggest that conventional-dose epirubicin may be effective in NSCLC treatment.…”
Section: Introductionmentioning
confidence: 86%
“…One significant predictor of treatment withdrawal was previous anthracycline use. Two prior studies in this medical center used epirubicin as part of first-line chemotherapy for advanced NSCLC [16,17]. Fourteen patients enrolled in the above two trials received cisplatin-based combination chemotherapy as their second-line therapy and weekly docetaxel as their third-line treatment.…”
Section: Discussionmentioning
confidence: 99%